2009
DOI: 10.1016/j.bcp.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of human enhancer of filamentation (HEF1) on serine 369 induces its proteasomal degradation

Abstract: Please cite this article as: Hivert V, Pierre J, Raingeaud J, Phosphorylation of human enhancer of filamentation (HEF1) on serine 369 induces its proteasomal degradation, Biochemical Pharmacology (2008Pharmacology ( ), doi:10.1016Pharmacology ( /j.bcp.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Y189 phosphorylation is implicated in focal adhesion; this is a proposed phosphorylation site for FAK and SRC kinases [114]. Phosphorylation of S296 by Aurora-A kinase is implicated in NEDD9 proteasomal degradation [115], cell spreading [116] and cell cycle control [30]. NEDD9 potentiates TGFβ signaling by recruiting the inhibitory SMAD6 and SMAD7 proteins, and preventing their interaction with TGFβ [63].…”
Section: Figurementioning
confidence: 99%
“…Y189 phosphorylation is implicated in focal adhesion; this is a proposed phosphorylation site for FAK and SRC kinases [114]. Phosphorylation of S296 by Aurora-A kinase is implicated in NEDD9 proteasomal degradation [115], cell spreading [116] and cell cycle control [30]. NEDD9 potentiates TGFβ signaling by recruiting the inhibitory SMAD6 and SMAD7 proteins, and preventing their interaction with TGFβ [63].…”
Section: Figurementioning
confidence: 99%
“…Protein phosphatase 2A (PP2A) binds and dephosphorylates both BCAR1 [109] and NEDD9 [110, 111]. PP2A negatively regulates the mitotic phosphorylation of BCAR1 [109].…”
Section: Introductionmentioning
confidence: 99%
“…PP2A negatively regulates the mitotic phosphorylation of BCAR1 [109]. PP2A is required for the de-adhesion-induced conversion from p115 to p105 kDa NEDD9 [110], potentially by targeting the Ser369 phosphorylation associated with this conversion [111]. The PRL (phosphatases of regenerating liver) subfamily of kinases are also linked to positive regulation of tumor growth; overexpression of PRL-1 was found to reduce BCAR1 levels [112], but inhibition of PRL phosphatases with a small molecule, thienopyridone, lead to BCAR1 cleavage [113].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the tyrosines, we note conservation of serine (S) 369 NEDD9 in the p130Cas and HEPL human, mouse and rat sequences. Previous studies have shown that this residue is critical for NEDD9 targeting by the proteasome [19] and plays a role in NEDD9-mediated cell spreading [20]. Leucine (L) 751 of NEDD9 that mediates binding to BCAR3/AND34/NSP2 [21] is conserved in p130Cas and this site has recently been confirmed to mediate the same interaction for p130Cas [22].…”
Section: Discussionmentioning
confidence: 96%